Agrupamentos sonoros plenos na música de simultaneidades acústicas e estruturais - Nogueira, Marcos Pupo [UNESP] (Univ Federal Goias, 2012)
The present article reflects about the concepts of linearity, space and acoustic complexity in the definition of sound grouping as a criticism to the linear concept of phraseology mainly when applied to the music of imitative texture or of complex simultaneities. It takes as examples works by Bach, Josquin des Prez and a fragment of "Lontano" by Ligeti, to study them in two distinct dimensions, simultaneous and interconnected: the acoustic dimension with its entire spectral complexity and the relational dimension which establishes the interaction among the figures in voices and texture layers with some kind of acoustic and structural simultaneity.
Full sound groupings in acoustic and structural simultaneity music
Keywords: Acoustic complexity; Imitative counterpoint and textural complexity; Linearity and sounding grouping